Clinical Audit : Supporting Post Detox Abstinence: Discussion of Relapse Prevention Medications by Community Addiction Services Prior to Referral for Inpatient Detoxification - Farheen Zahra; John Barker; Paul Briley (BJPsych Open, 2025)
Aims: Without a plan to support ongoing abstinence, detoxification (“detox”) could increase, rather than reduce, risks to a patient. Before referring for inpatient detox from alcohol or opioids, community teams are expected to discuss relapse prevention medications (RPMs) with patients, as part of their wider support plan.